DEICTIC EXPRESSIONS IN PRESIDENT BENIGNO AQUINO III’S EULOGY FOR THE FALLEN PNP-SAF TROOPERS: A STYLISTIC ANALYSIS - Purcia, Erwin L (MATTER: International Journal of Science and Technology, 2015)
This study was conducted to determine the deictic expressions used by President Benigno Aquino III’s eulogy in the necrological service rendered among the fallen 44 SAF troopers who died heroically in saving the country, Philippines. Specifically, this was geared towards determining how President Benigno S. Aquino III deployed persons, time, space and social relationships in the deictic field of the English translation of his Eulogy, hence, identify what meaning and effect are shaped and conveyed by the President’s use of deictic expressions in the speech to condole the bereaved families of the Fallen 44. The study made use of stylistic analysis which was utilized to determine the condoling meaning of each deictic expression used by the president. Guided by Fillmore (1997) and Al Azzawi (2011), categories of deictic expressions were delineated to specific functions they all convey. The results revealed that with the guide of the framework anchored on Hank’s (2005) notion of deictic field and Buhler’s (1934) notions on deictic centre or origo, the paper found that PNoy extensively and strategically made use of referring expressions in order to set up the deictic field in a way that he could serve his purpose of delivering the eulogy. PNoy’s extensive and strategic use of personal, temporal and spatial and social deictic expressions very effectively sets up the deictic field so that, in terms of the persons, time, place and social relationships involved and referred to, the bereaved/Filipino people would be able to understand the stand of the government as regards the issue and be ableto deliver justice among the Fallen troopers and judge the President and his government as one in this quest for truth. Through this, PNoy was able to dichotomize not only two different kinds of persons, two different periods of time, but also two different relationships with the Filipino people and himself and the government in a more advantaged and privileged light.